New bis-andrographolide ether from androgphis paniculata nees and evaluation of anti-HIV activity - Reddy, V. L. N.; Reddy, S. M.; Ravikanth, V.; Krishnaiah, P.; Goud, T. V.; Rao, T. P.; Ram, T. S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Venkateswarlu, Y (Natural Product Research, 2005)
Novel bis-andrographolide ether (1) and six known compounds andrographolide, 14-deoxy-11,12-didehydroandrographolide, andrograpanin, 14-deoxyandrographolide, (+/-)-5- hydroxy-7,8-dimethoxyflavanone, and 5-hydroxy-7,8-dimethoxyflavone have been isolated from the aerial parts of Andrographis paniculota and their structures were established by spectral data. All the isolates were tested for the anti-HIV and cytotoxic activity.
Keywords: Acanthaceae; Andrographis paniculata; anti-HIV; bis-andrographolide ether; Cytotoxic activity

Factors influence on growth, don and niv production by two species of fusarium isolated from finger millets [eleusine coracana l.] - Vankudoth, Koteswara Rao; Penugonda, Shilpa; Sivadevuni, Girisham; Reddy, S. M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
ABSTRACT Objective: The present investigations (In vitro) on an influence of different synthetic and food based [flour] media, pH, temperature and microbial nutrients on growth, Deoxynivalenol [DON] and Nivalenol [NIV] production by Fusarium aethiopicum and F. culmorum was carried out. Methods: Fusarium species associated with the finger millets were isolated and identified phenotypically and further confirmed by molecular methods by Polymerase Chain Reaction [PCR]. Monosporic seven day old F. aethiopicum and F. culmorum were grown in CYA broth and incubated at 27±2°C on rotary shaker for 21 days at 120 rpm. At the end of 21 day incubation period, cultures were harvested for determination of fungal biomass. The resultant culture filtrates were extracted twice with ethyl acetate and concentrated to get and final concentration of 1 ml in methanol and employed for RP-HPLC analysis for detection of DON and NIV production. Results: Finger millets flour medium induced the highest amount of mycelial growth, DON and NIV production by F. aethiopicum. However, F. culmorum achieved highest amount of hyphal growth, DON and NIV production under the influence of yeast extract sucrose [YES] medium. Maize flour medium, rice flour medium and sorghum flour medium was next preffered substrates. Optimum pH of 5.5-6.5 and temperature of 20-35°C for growth, DON and NIV production was observed. Both the species of Fusarium failed to grow and produce toxins at pH 2.5-3.5 and temperature of 40°C. Yeast extract was most favorable for maximum DON and NIV production, which increased with an increase in its concentration. On the other hand, malt extract and beef extract induced good growth and mycotoxin production at comparatively higher concentration in both the species of Fusarium under study. Conclusion: Comparatively food based media were the better substrates than synthetic media for both growth and DOIN and NIV production by two species of Fusarium under investigation. A positive correlation coefficient [r] on growth [0.458], DON [0.744] and NIV [0.882] was recorded among the media and both the species of Fusarium. Keywords: Finger millets, F. aethiopicum, F. culmorum, Synthetic media, pH, Temperature, Microbial nutrients, DON, NIV, HPLC

Efficacy of food preservatives and volatile compounds in the control of ochratoxin a production by penicillium species - Vankudoth, Koteswara Rao; Rao, K. Narasimha; Sivadevuni, Girisham; Reddy, S. M. (Proceedings of the National Academy of Sciences, India - Section B: Biological Sciences, 2015)
In the present investigation different volatile compounds and food preservatives were tested for their efficiency in the control of growth and ochratoxin A (OTA) production by Penicillium verrucosum and Penicillium nordicum. Volatiles such as phenols and formic acid which have no residual effect were proved to be effective in checking the growth and OTA production by both the species of Penicillium under study. Vapours of phenols and formic acid significantly inhibited OTA produced by P. verrucosum, while aniline and toluene inhibited the OTA production by P. nordicum to a significant level. A positive correlation coefficient was observed between the growth and toxin production by P. verrucosum (0.55) and P. nordicum (0.66) against different volatile compounds tried. Among food preservatives, sodium acetate and sodium metabisulphate were responsible for total inhibition of OTA production by P. verrucosum at 150 lg/ml concentration. P. nordicum proved to be comparatively more resistant to these substances than P. verrucosum. In conclusion of present investigation, phenol, formic acid, amyl alcohol, propionic acid, sodium acetate and sodium metabisulphate were found to be effective in checking the growth and OTA production by both the species of Penicillium under investigation, and can be exploited in protecting the poultry feed from unwanted mould growth and mycotoxin production.

Culture conditions for the production of thermostable lipase by thermomyces lanuginosus - Sreelatha, B.; Vankudoth, Koteswara Rao; Kumar, R. Ranjith; Girisham, Sivadevuni; Reddy, S. M. (Journal of Basic and Applied Sciences, 2016)
In the present investigation lipase production by three strains of thermophilic Thermomyces lanuginosus (GSLMBKU-10, GSLMBKU-13 and GSLMBKU-14) was carried out in submerged fermentation process. Olive oil and triacetin (0.1%) were added to the basal medium, which stimulated the lipase production. The maximum lipase was produced by GSLMBKU-10 and GSLMBKU-13 in yeast extract starch medium supplemented with triacetin (0.1%). The optimum pH was recorded at 6.0, 6.5 and 7.0 by GSLMBKU-10, GSLMBKU-13 and GSLMBKU-14 respectively. T. lanuginosus GSLMBKU-10 strains failed to produce lipase at pH 8.0. The optimum temperature for lipase production was observed at 45 °C by GSLMBKU-14 and GSLMBKU-10, while that for GSLMBKU-13 was at 50 °C. The marginal temperature ranged from 45 °C to 50 °C for both lipase production and vegetative growth by the three strains of T. lanuginosus under study. In conclusion, the GSLMBKU-13 strain was comparatively superior in the production of lipase than the other two strains under investigation.